Study on corrosion behavior of 13Cr gate valve using weld deposited gate and seat in well operation environments. (June 2023) - Long, Yan; Jiang, Wenchun; Chen, Gang; Luo, Jinheng; Fan, Yujie; Jin, Qiang; Xie, Junfeng; Feng, Yaorong; Xie, Jianfeng
Highlights: The corrosion on the sealing surface of the valve body was related to the galvanic corrosion in the spent acid. Intergranular corrosion along the interface of the weld deposit for the gate and seat was derived from carbides. The formation of carbides was induced by the C element diffusion from alloy deposits during the spray weld. Abstract: The different types of corrosion behavior occurred on a 13Cr gate valve using weld deposited gate and seat after about sixteen months of service in an oilfield in China, resulting in the leakage failure. In this study, the corrosion causes were investigated through visual inspection, mechanical performance testing, scanning electron microscopy, energy dispersive spectrometer and electrochemical analysis. The results demonstrated that the corrosion on the sealing surface of the valve body was related to the galvanic corrosion between the 304 SS ring gasket and 13Cr SS ring groove, which presented a significant potential difference in the spent acid environment. In addition, due to the C element diffusion from deposits during the spray weld on the surface of the gate and seat, a large amount of Cr enrich carbides were formed at the prior austenite grain boundaries in the 13Cr SS matrix side, which further induced the intergranular corrosion and cracking along the interface in service.